Activation of a G protein-coupled receptor through indirect antibody-mediated tethering of ligands. Issue 6 (11th October 2021) - Cheloha, Ross W.; Fischer, Fabian A.; Gardella, Thomas J.; Ploegh, Hidde L.
Abstract : The use of antibodies to target membrane receptors enables specific and potent activation. But antibodies with appropriate specificity can be lacking. We present methods for targeting receptors without target-specific antibodies. Abstract : Antibodies raised against many cell surface proteins, including G protein-coupled receptors, remain important tools for their functional characterization. By linking antibodies to ligands for cell surface proteins, such adducts can be targeted to the surface of a cell type of choice. Site-specific functionalization of full-size antibodies with synthetic moieties remains challenging. Here we present new approaches in which single domain antibodies (known as VHHs or nanobodies) that target either cell surface proteins or conventional antibodies are used to indirectly deliver ligands for GPCRs to their sites of action. The combination of high yield production of nanobodies, facile site-specific functionalization, and compatibility with commercially available mouse and rabbit antibodies should enable wide application of this approach.